The Effect of Principal’s Leadership and Certification on the Quality of High School Teacher’s Performance - Yanti, Eka Dharma; Arafat, Yasir; Rahman, Andi (Journal of Social Work and Science Education, 2023)
Education is a strategic component of a country in developing civilization and the quality of the nation’s capabilities that are dignified, prosperous and advanced. This study aims to determine the effect of the principal’s leadership style and way of making decisions, and of guiding teachers in carrying out the teaching process and the government’s efforts that are committed to improving the quality of education by certifying PNS and NON PNS teachers on teacher’s performance. The study used a questionnaire to obtain data and analyze using simple regression analysis methods and multiple regression analysis. The results of this study showed that the principal’s leadership and teacher certification significantly affect teacher’s performance.